Outcomes of Trabeculectomy With and Without Mitomycin C in Pseudoexfoliative Glaucoma Compared With Mitomycin C in Primary Open Angle Glaucoma. - Lopes, AS (2019)
The aim of this study was to evaluate the outcomes of trabeculectomy with mitomycin C (MMC) in patients with Pseudoexfoliative Glaucoma (PXG) and compare the results with the outcomes of trabeculectomy without MMC in PXG and with MMC in Primary Open Angle Glaucoma (POAG). Ninety eyes (76 patients) submitted to trabeculectomy were included in a one-year retrospective study. Fifty-eight eyes with PXG were divided into group 1 (28 eyes) and group 2 (30 eyes), with and without MMC application respectively. Then, the group 1 results were compared with 32 eyes with POAG that performed trabeculectomy with MMC (group 3). Main outcome measures were intraocular pressure (IOP), number of IOP lowering medications, rate of bleb failure (encapsulation, flattening and/or vascularization) and the number of eyes submitted to surgical procedures after trabeculectomy (needling, 5-fluorouracil (5FU) or 2nd trabeculectomy). Results revealed that compared to trabeculectomy with MMC in POAG and trabeculectomy with MMC in PXG, trabeculectomy without MMC in PXG leads to higher IOP (preoperative mean ± standard deviation [SD] was 28.6 ± 5.4 mmHg in group 1, 32.2 ± 8.2 mmHg in group 2 and 26.1 ± 6.5 mmHg in group 3; and after one year was 13.9 ± 3.9 mmHg in group 1, 16.1 ± 5.9 mmHg in group 2 and 12.5 ± 4.0 mmHg in group 3); higher number of IOP lowering medications (preoperative mean ± SD was 3.1 ± 0.60 in group 1, 2.8 ± 0.81 in group 2 and 3.4 ± 0.76 in group 3; and after one year was 1.1 ± 1.1 in group 1, 1.1 ± 1.0 in group 2 and 0.33 ± 0.89 in group 3); higher prevalence of bleb failure (47% in group 1, 53% in group 2, and 18% in group 3); and increased participation in surgical procedures following trabeculectomy (47% in group 1, 57% in group 2, and 6% in group 3). We concluded that trabeculectomy without MMC in PXG had the worst surgical outcome. Thus, PXG appears to be a potential risk factor for filtration bleb failure. Therefore, it could be considered in surgical protocols of MMC application.